Sand spit rhythmic development: a potencial record of wave climate variations ? Arcay spit, western coast of France - Allard, J. (2010)
This study aims at showing the sedimentary and geomorphological records of wave climate variations by spits. The studied spit (Arçay Spit) is located on the French Atlantic coast and has displayed a rapid elongation since the beginning of the 19th century that potentially represents a two century-long wave climate record. Wave climate and spit growth relationships are studied from two complementary methods: (1) numerical modelling of wave and longshore transport temporal and spatial variabilities, and (2) morphological monitoring based on the analysis of 4 historical maps (1811–1945), 8 aerial photographs (1945–2000) and 17 satellite SPOT images (1987–2005). Results at seasonal to interannual time-scales show that the sand spit area gain variations are the result of variations in longshore transport, themselves modulated mainly by wave height. Moreover, energetic swells seem to cause massive sand accumulation and spit elongation, whereas less energetic swells appear to be responsible for small sand accumulation and spit curvature. At longer time scale (decades to centuries), increasing spit growth phases are also synchronised with periods of energetic swells or high storm surge frequency. These results suggest that wave climate variations are the main factor controlling spit morphological evolutions.